Pengembangan Umkm untuk Meningkatkan Kesejahteraan Masyarakat di Desa Pagaruyung, Kampar, Riau - Erpiani Siregar; Yusmarini Yusmarini; Usman Pato; Dewi Fortuna Ayu; Shanti Fitriani; Emma Riftyan; Yossie Kharisma Dewi; Bintang Sipartogi Panjaitan; Yusni Maulida (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Pagaruyung Village, Kampar, Riau, has great potential in the agricultural sector, particularly in the abundant production of pineapples. However, these agricultural products have not been fully utilized to improve the welfare of the community. One effort to optimize this potential is by developing Micro, Small, and Medium Enterprises (MSMEs) based on pineapple processing. The objective of this community service activity is to improve the capacity of MSME actors in business management to support the welfare of the community in Pagaruyung Village, Kampar, Riau. The activity involved 16 MSME members and village officials through pre-tests, material delivery, practice, interactive discussions, and post-tests. The results of the activity showed an increase in participants' knowledge and skills in business management, financial recording, product innovation, packaging techniques, and digital marketing strategies. A comparison of the pre-test and post-test results showed an increase in the average score of the participants, which was an indicator of the success of the training. In addition, a community of MSME actors in Pagaruyung Village was formed as a forum for collaboration and sustainable business development with the support of village officials. This activity had a positive impact not only on improving individual capacity but also on strengthening village MSME institutions, which is expected to contribute to improving the community's welfare in a sustainable manner.